Pharmacological aspects of Nerium indicum Mill: A comprehensive review - Dey, Priyankar; Chaudhuri, Tapas Kumar (Pharmacognosy Reviews)
Phytomedicine is the oldest medical practice known to man. Since the dawn of mankind, various plant resources are used to cure different diseases and also for a long and healthy life. The ancient knowledge of plant based medicine has transferred from generations to generations and accumulated as ethnopharmacological knowledge among different ethnic groups. India is the spanning bed of traditional phytomedicinal system where Ayurveda was born out of the knowledge of traditional medicine. In various other countries of South‑Eastern Asia, South America, and in Arabian countries, still today, a great number of people rely primarily on phytomedicines to cure diseases. In the complementary and alternative medicinal systems, Nerium indicum is one such plant which is famed for its therapeutic efficiency in different diseases globally. In the present time, when the pharmaceutical companies are concentrating more toward the plant based traditional medicines to avoid the side‑effects and resistance against synthetic drugs, N. indicum has proved its efficiency in different disease models. Therefore, this review comprehensively covers the medicinal and pharmacological activities of different parts of the plant N. indicum.
Keywords: Anvirzel; ethnopharmacology; herbal medicine; Nerium indicum; oleander; oleandrin